2022
DOI: 10.19044/esj.2022.v18n22p159
|View full text |Cite
|
Sign up to set email alerts
|

Existing Practicies of Parent-child Communication on Sex-related Matters among Households in Ondo State, Nigeria

Abstract: Adolescents' sexual and reproductive health remain global public health concerns particularly in Sub-Saharan. Undoubtedly, parent-child communication remains a vital means by which parents transmit cultural values and monitor the sexual health of their children. The nature and the quality of sexual conversations that subsist in the family are critical factors in the prevention of sexual risk-taking behaviour among adolescents. Therefore, this paper investigated the existing practices of parent-child communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition, mothers are considered appropriate initiators to discuss sexual topics with their adolescent children. Male and female adolescents perceive a mother as their primary source of communication to discuss sexuality [57], [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mothers are considered appropriate initiators to discuss sexual topics with their adolescent children. Male and female adolescents perceive a mother as their primary source of communication to discuss sexuality [57], [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, the conversation continues to focus more and more on abstinence, sometimes laced with cultural and religious biases [ 18 , 19 , 31 ], without reflecting the contemporary reality of adolescents about sexual issues. Additionally, a number of factors or barriers that prevent effective parent-child discussions about SRH have been examined in research conducted in Ghana [ 27 , 32 34 ], Ethiopia [ 15 , 19 , 35 , 36 ], Kenya [ 29 ], South Africa [ 37 , 38 ], and Nigeria [ 8 , 28 , 30 ]. Even though these studies have demonstrated some effects, there is little empirical evidence about the situational context of parent-adolescent communication regarding SRH issues in urban slums.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, a large body of literature has shown the positive effect of parent-adolescent communication on sexual issues [23][24][25][26]. Evidence from Sub-Saharan Africa (SSA) suggests that parent-child dialogue on SRH issues is becoming more common [8,14,[27][28][29][30]. However, the conversation continues to focus more and more on abstinence, sometimes laced with cultural and religious biases [18,19,31], without reflecting the contemporary reality of adolescents about sexual issues.…”
Section: Introductionmentioning
confidence: 99%